2016
DOI: 10.1515/amm-2016-0139
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance and Pitting Behaviour of Low-Carbon High-Mn Steels in Chloride Solution

Abstract: CorrosIon rEsIstanCE and pIttIng bEhavIour of low-Carbon hIgh-Mn stEEls In ChlorIdE solutIonCorrosion resistance of the X4MnSiAlNbTi27-4-2 and X6MnSiAlNbTi26-3-3 type austenitic steels, after hot deformation as well as after cold rolling, were evaluated in 3.5% NaCl solution using potentiodynamic polarization tests. A type of nonmetallic inclusions and their pitting corrosion behaviour were investigated. Additionally, the effect of cold deformation on the corrosion resistance of high-Mn steels was studied. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The twins represent regions characterized by different potential from the matrix and this leads to the increase in the corrosion current density. Results of our previous works [9,10] confirmed that corrosion pits nucleated mainly at grain boundaries and deformation bands in cold deformed steels. Corrosion resistance of grain boundaries is poor because of high dislocation density present at these regions [17,33].…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…The twins represent regions characterized by different potential from the matrix and this leads to the increase in the corrosion current density. Results of our previous works [9,10] confirmed that corrosion pits nucleated mainly at grain boundaries and deformation bands in cold deformed steels. Corrosion resistance of grain boundaries is poor because of high dislocation density present at these regions [17,33].…”
Section: Introductionsupporting
confidence: 55%
“…Thus, better corrosion resistance of this steel can be also probably related to higher amount of AlN inclusions (and smaller quantity of MnS inclusions). Based on our previous results of potentiodynamic tests [9,10] it can be observed that corrosion pits did not form on Al 2 O 3 inclusions during corrosion tests in 0.1M NaOH in opposite to 3.5% NaCl solution. Park et .…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations